Catastrophic costs among tuberculosis‐affected households in Zimbabwe: A national health facility‐based survey. Issue 10 (3rd August 2021) - Timire, Collins; Ngwenya, Mkhokheli; Chirenda, Joconiah; Metcalfe, John Z; Kranzer, Katharina; Pedrazzoli, Debora; Takarinda, Kudakwashe C.; Nguhiu, Peter; Madzingaidzo, Geshem; Ndlovu, Kwenzikweyinkosi; Mapuranga, Tawanda; Cornell, Morna; et al.
Abstract: Objectives: To determine the incidence and major drivers of catastrophic costs among TB‐affected households in Zimbabwe. Methods: We conducted a nationally representative health facility‐based survey with random cluster sampling among consecutively enrolled drug‐susceptible (DS‐TB) and drug‐resistant TB (DR‐TB) patients. Costs incurred and income lost due to TB illness were captured using an interviewer‐administered standardised questionnaire. We used multivariable logistic regression to determine the risk factors for experiencing catastrophic costs. Results: A total of 841 patients were enrolled and were weighted to 900 during data analysis. There were 500 (56%) males and 46 (6%) DR‐TB patients. Thirty‐five (72%) DR‐TB patients were HIV co‐infected. Overall, 80% (95% CI: 77–82) of TB patients and their households experienced catastrophic costs. The major cost driver pre‐TB diagnosis was direct medical costs. Nutritional supplements were the major cost driver post‐TB diagnosis, with a median cost of US$360 (IQR: 240–600). Post‐TB median diagnosis costs were three times higher among DR‐TB (US$1, 659 [653–2, 787]) than drug DS‐TB‐affected households (US$537 [204–1, 134]). Income loss was five times higher among DR‐TB than DS‐TB patients. In multivariable analysis, household wealth was the only covariate that remained significantly associated with catastrophic costs: The poorest households had 16 times the odds of incurring catastrophic costs versus the wealthiest households (adjusted odds ratio [aOR: 15.7 95% CI: 7.5–33.1]). Conclusion: The majority of TB‐affected households, especially those affected by DR‐TB, experienced catastrophic costs. Since the major cost drivers fall outside the healthcare system, multi‐sectoral approaches to TB control and linking TB patients to social protection may reduce catastrophic costs.